Inflammation‐Related Genetic Variations and Survival in Patients With Advanced Non–Small Cell Lung Cancer Receiving First‐Line Chemotherapy. Issue 3 (22nd April 2014) - Pu, X; Hildebrandt, M A T; Lu, C; Roth, J A; Stewart, D J; Zhao, Y; Heist, R S; Ye, Y; Chang, D W; Su, L; Minna, J D; Lippman, S M; et al.
<x xml:space="preserve">Abstract</x> Accurate prognostic prediction is challenging for patients with advanced‐stage non–small cell lung cancer (NSCLC). We systematically investigated genetic variants within inflammation pathways as potential prognostic markers for advanced‐stage NSCLC patients treated with first‐line chemotherapy. A discovery phase in 502 patients and an internal validation phase in 335 patients were completed at the MD Anderson Cancer Center. External validation was performed in 371 patients at Harvard University. A missense single‐nucleotide polymorphism (SNP) in the gene encoding the major histocompatibility complex class II, DO‐β chain (HLA‐DOB:rs2071554), predicted to influence protein function, was significantly associated with poor survival in the discovery (hazard ratio (HR): 1.46; 95% confidence interval (CI): 1.02–2.09), internal validation (HR: 1.51; 95% CI: 1.02–2.25), and external validation (HR: 1.52; 95% CI: 1.01–2.29) populations. KLRK1:rs2900420 was associated with reduced risk in the discovery (HR: 0.76; 95% CI: 0.60–0.96), internal validation (HR: 0.77; 95% CI: 0.61–0.99), and external validation (HR: 0.80; 95% CI: 0.63–1.02) populations. A strong cumulative effect on overall survival was observed for these SNPs. Genetic variations in inflammation‐related genes could have potential to complement prediction of prognosis. Clinical Pharmacology & Therapeutics (2014); 96 3, 360–369. advance online publication 04 June 2014. doi:10.1038/clpt.2014.89